Synovial Immunophenotype and Anti–Citrullinated Peptide Antibodies in Rheumatoid Arthritis Patients: Relationship to Treatment Response and Radiologic Prognosis - Orr, Carl; Najm, Aurelie; Biniecka, Monika; McGarry, Trudy; Ng, Chin‐Teck; Young, Francis; Fearon, Ursula; Veale, Douglas J. (Arthritis & rheumatology (Hoboken, N.J.), 2017)
Serum anti-citrullinated peptide antibodies (ACPAs) may be present before the development of rheumatoid arthritis (RA) and may be predictive of more severe, erosive disease. This study was undertaken to examine the synovial tissue immunophenotype according to ACPA status in patients with RA, as well as the response to treatment and erosion status. Consecutive RA patients were prospectively recruited and underwent clinical and serologic assessments before and after treatment. Radiologic assessment was performed at the time of clinical follow-up. Synovial tissue was immunostained for specific markers of B cells (CD19), T cells (CD3, CD4, and CD8), macrophages (CD68), and blood vessels (factor VIII). Serum CXCL13 levels were quantified by enzyme-linked immunosorbent assay. Synovial tissue sections were analyzed for immunophenotype according to ACPA status, using a validated semiquantitative scoring method, and also analyzed for the presence of lymphoid aggregates. Response to treatment with nonbiologic or biologic disease-modifying antirheumatic drugs was assessed using the European League Against Rheumatism (EULAR) response criteria. In total, 123 subjects (78 ACPA+) were included. Compared to ACPA- RA patients, synovium from ACPA+ RA patients was characterized by significantly higher levels of CD19+ B cells and CD3+ and CD8+ T cells (each P < 0.05), and CD19+ B cell levels were significantly higher in patients who were naive to treatment. The CD19+ B cell infiltrate level was higher in patients with erosions at follow-up (P = 0.0128). Levels of lymphoid aggregates of CD19+ B cells were significantly higher in ACPA+ patients (P < 0.05), and this was associated with increased serum CXCL13 levels. The EULAR response was significantly associated with the level of CD3+ T cell infiltrates (P < 0.05), while CD68+ macrophage and CD8+ T cell levels were predictive of the response to tumor necrosis factor inhibitors (P < 0.05). The results of this prospective study demonstrate that the levels of synovial B cell infiltrates and lymphoid aggregates were significantly higher in ACPA+ RA patients, especially those who were naive to treatment. In addition, ACPA+ subjects developed more erosions during progression of the disease and had higher serum levels of CXCL13. The EULAR response to therapy in ACPA+ RA patients was associated with increased levels of T cell and macrophage markers.